Antecedents of Customer Loyalty Using Social Exchange Theory in Building Customer Loyalty in the Coffee Shops - Pringgo Syahputro; Muhammad Zulkifli Amanda; Karina Aprilia Ristanti (JIMF (Jurnal Ilmiah Manajemen Forkamma), 2022)
Visiting coffee shops has become a trend and culture in Indonesian society, especially in Greater Jakarta (Jabodetabek). It results in a rapidly growing coffee shop industry with high competition. Many local and international coffee shops are expanding its store in Greater Jakarta. Many previous studies have examined the factor affecting customer loyalty before and during the pandemic period. With the better condition of pandemics and significant reduction of social restriction, this study aims to analyze the factor affecting customer loyalty. Service quality, store atmosphere, price fairness, and customer satisfaction are those factors. An SEM path analysis is used to examine the four hypotheses that have been proposed. The findings show that service quality, store atmosphere, and price fairness affect customer satisfaction. Also, customer satisfaction has an effect on customer loyalty. The findings also support that service quality is a significant driver in the coffee shop industry in Greater Jakarta.